Suitability of selected legume (Vachellia spp.) tree species for forest restoration in the Central Ethiopian highlands - FISSEHA ASMELASH; EMEBET GETACHEW (Nusantara Bioscience, 2022)
Abstract. Asmelash F, Getachew E. 2022. Suitability of selected legume (Vachellia spp.) tree species for forest restoration in the Central Ethiopian highlands. Nusantara Bioscience 14: 195-202. This study aimed to evaluate the comparative suitability of the legume tree species viz., Vachellia abyssinica (Hochst. ex. Benth.) Kyal. & Boatwr., Vachellia etbaica (Schweinf.) Kyal. & Boatwr., Vachellia lahai (Steud. & Hochst. ex Benth.) Kyal. & Boatwr., and Vachellia seyal (Delile) P.J.H.Hurter for restoring forests in Central Ethiopian highlands. The suitability of three accessions of V. seyal was also compared. The correlation between root nodule number and root Arbuscular Mycorrhizal Fungi (AMF) colonization (RC) and seedlings’ growth variables were computed, and the effect of seedling age on nodule number and RC was determined. Seedlings were grown for nine months on degraded local soil in a mesh house in central Ethiopia. We measured shoot height, shoot fresh weight, rooting depth, root nodule number, and RC in the third and ninth months. The one-way ANOVA results indicated that tree species and/or accession (for V. seyal) had a significant (p<0.05) effect on all the measured variables except shoot height and rooting depth at the ninth month. Generally, nodule number and RC increased with seedling age. However, according to the independent t-test results, significant (p<0.05) differences were recorded for V. abyssinica, with a 57.16% reduction in nodule number, and V. seyal accession-1, with a 418.52% increase in RC. The Spearman’s rank correlation results indicated that the correlation between nodule number and RC was weak and non-significant (p>0.05) both in the third and ninth months. Based on the measured growth variables, nodule number (N-fixation potential), and RC, V. etbaica was the least suitable species for forest restoration in central Ethiopian highlands. The remaining species/accessions are comparably suitable. The V. abyssinica lost its comparative fitness with seedling age, maybe because it is a provenance far away from central Ethiopia. However, V. seyal accession-3, the furthest provenance, has performed much better. The legume trees of Ethiopia are less studied. Their role as environmental engineers could be better understood by knowing more about their root traits. Therefore, this study could motivate future research in this regard. Long-term experiments are required to consider more legume tree species and provenances in the future.